IMPACT OF DIGITALIZATION ON PROFITABILITY OF PUBLIC AND PRIVATE SECTOR BANKS IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
The study has been emphasized on the digital banking impact on the operational profitability of the select public and private sector banks. The study has considered the 3G and 4G period. The study has considered the State bank of Indian from the public sector bank and HDFC bank from private sector. The study has considered the secondary data from the period 2012- 13 to 2017-18